Checklist for sustainable landscape management : final report of the EU concerted action AIR3-CT93-1210 : the landscape and nature production capacity of organic/sustainable types of agriculture - Mansvelt, J. D. van (Jan Diek); Lubbe, M. J. van der.; ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 1999)
This work is an interdisciplinary, cross-cultural, widely-calibrated checklist for EU sustainable landscape management, which is intended to serve both as an analytical tool of reference as well as a design tool for local, regional and European policy making on sustainable developments. The tool has been developed out of a multidisciplinary study in EU countries which was designed to find out what would be the overall requirements for a sustainable management of the landscape of rural areas. Could these stipulations be brought together in a comprehensive system with sufficient consistency to comply with the notion that the landscape is an entity, which should be managed accordingly? Cooperation of the scientific experts with those involved in the practical side, and alternating plenary reporting with subgroup visits to farms in the rural landscapes of the participants' countries, allowed for the development of some truly interdisciplinary teamwork. Organic agriculture has been included to find out how organic agriculture contributes to the rural landscape.
Preface. Summary. 1. Introduction. Background and problem statement. Objectives. Approach. Structure of the report. 2. Research Methods. Outline of a unifying concept. On the complementarity of interdisciplinary Holism and disciplinary reductionism. Dissemination of results. 3. Results. Introduction. Explanation of checklist. Conclusions. 4. Performances of Organic Agriculture. Theory and literature. Empirical data collected from literature. 5. Uses and Users. Overview of possible uses and users. Indicative links with funding. 6. References. Annex 1: Participants. Annex 2: Checklist's compliance with other standards for sustainable and organic agriculture.
Includes bibliographical references (pages 157-175).
Print version record.
Elsevier
Keywords: Land use, Rural -- Environmental aspects -- European Union countries -- Planning; Sustainable agriculture -- European Union countries -- Planning; Landscape protection -- Economic aspects -- European Union countries -- Planning; Sustainable development -- European Union countries -- Planning; NATURE -- Natural Resources; BUSINESS & ECONOMICS -- Environmental Economics; BUSINESS & ECONOMICS -- Green Business; Landschapsbouw; Duurzame ontwikkeling; Duurzame landbouw; Sustainable agriculture -- Planning; Sustainable development -- Planning; Europe -- European Union countries; Electronic books